Rice Straw and Titonia Compost Granular Formation to Improve Onion Production in Regosol - ulfia fadilla (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
Utilization of granule compost from rice straw (JP) and titonia (T) as a nutrient enrichmen for Regosol. Regosol has low nutrient content, especially in macro nutrient then it important to incease nutrient content for Onion cultivation. This research aims to study the effect of application granular compost from rice straw and titonia to the chemical properties and onion production. The research was conducted at the Wire House and Soil Chemistry Laboratory, Faculty of Agriculture, Andalas University. The design used was a completely randomized design (CRD) consisting of 4 treatments and 3 replications. The level of granul compost is 0 ton / ha; 7.5 tons / ha; 15 ton / ha; and 22.5 ton / ha. The results showed that giving JP and T granule compost improved soil chemical properties such as C-organic, N-total, P-available and K-dd soil. Aplication granular compost 22.5 tons / ha increased wet weight, dry weight, number and diameter bulb.